Binding of Cr2-transferrin to Transferrin Receptor Enhances the Rate of Chromium Loss and Is Dependent on the Conformation of Transferrin (P24-053-19). (13th June 2019) - Edwards, Kyle; Kim, Hannah; Boyd, Cortlyn; Vincent, John
Abstract: Objectives: Transferrin, Tf, the protein transports iron from the blood to the tissues via endocytosis, is believed to also transport chromium(III), Cr(III). Recently, the release of Cr(III) from Tf has been postulated to be too slow for appreciable quantities of Cr(III) to be released during the lifetime of an endosome. The objective of this work was to measure the rate of Cr(III) release from human serum Tf as a function of Tf confirmation and as the transferrin-transferrin receptor (TfR) complex. Methods: Cr(III) was added to apoTf in a buffered solution at pH 7.4 containing 25 mM bicarbonate at 37 °C. After time intervals, ultraviolet spectra were collected, or aliquots were removed and frozen for analysis by electron paramagnetic resonance (EPR) spectroscopy, which can distinguish free Cr(III) and Cr(III) bound to the two metal binding sites of Tf. To model the acidification of the endosome that triggers release of metal ions from Tf, the Cr(III)2 -Tf solutions were acidified by the addition of hydrochloric acid to pH 4.5 or 5.5. At time intervals after acidification, samples were again analyzed by ultraviolet and EPR spectroscopies. Similar studies were performed in the presence of Tf receptor, which binds two equivalents of Cr(III)2 -Tf. Results: The loss of Cr(III) from the two metal-binding sites of Tf occur at different rates. Different confirmations of the Cr2 -Tf complex exist depending on the conditions of Cr2 -Tf formation. The conformation that forms rapidly under physiological conditions loses Cr(III) faster than conformations that form over longer periods of time. Binding of Cr(III)2 -Tf to TfR facilitates the release of Cr. Conclusions: The conformation of Cr(III)2 -transferrin that forms under physiological conditions when complexed with transferrin receptor can release Cr at physiologically significant rates consistent with transferrin serving as the major Cr(III) transport agent between the blood stream and tissues. Funding Sources: The University of Alabama College of Arts and Sciences Research Award.